Full annual monitoring of Subantarctic Emiliania huxleyi populations reveals highly calcified morphotypes in high-CO2 winter conditions - Rigual-Hernandez, AS; Trull, TW; Flores, JA; Nodder, SD; Eriksen, R; Davies, DM; Hallegraeff, GM; Sierro, FJ; Patil, SM; Cortina, A; Ballegeer, AM; Northcote, LC; et al. (Scientific Reports, 2020)
Ocean acidification is expected to have detrimental consequences for the most abundant calcifying phytoplankton species Emiliania huxleyi. However, this assumption is mainly based on laboratory manipulations that are unable to reproduce the complexity of natural ecosystems. Here, E. huxleyi coccolith assemblages collected over a year by an autonomous water sampler and sediment traps in the Subantarctic Zone were analysed. The combination of taxonomic and morphometric analyses together with in situ measurements of surface-water properties allowed us to monitor, with unprecedented detail, the seasonal cycle of E. huxleyi at two Subantarctic stations. E. huxleyi subantarctic assemblages were composed of a mixture of, at least, four different morphotypes. Heavier morphotypes exhibited their maximum relative abundances during winter, coinciding with peak annual TCO2 and nutrient concentrations, while lighter morphotypes dominated during summer, coinciding with lowest TCO2 and nutrients levels. The similar seasonality observed in both time-series suggests that it may be a circumpolar feature of the Subantarctic zone. Our results challenge the view that ocean acidification will necessarily lead to a replacement of heavily-calcified coccolithophores by lightly-calcified ones in subpolar ecosystems, and emphasize the need to consider the cumulative effect of multiple stressors on the probable succession of morphotypes.